Employee Motivation in Private Schools of Birgunj Metropolitan City - Dwibedi, Lalan (Dristikon: A Multidisciplinary Journal, 2020)
The paper aims to find out which motivational factors can effectively increase employee motivation, to know whether the delivered incentives are sufficient or not and also to know effect of incentives in their performance. Motivation and its influence on organizational performance has always remained highly researched area and have gone through many discussions and repetitions. In this research both exploratory and descriptive research design used to explore employee motivation issues in schools of Birgunj Metropolitan city. Data was collected through Questionnaire and content analysis. It is revealed that motivating factors and motivational packages has positive impact on employee motivation in private schools. The responses of this paper were analyzed and found that monetary and non-monetary both incentives are active tools to motivate workforce. Good salary and allowances have been used as monetary motivators, while, good working environment, freedom to work and recognition as non-monetary motivator. This study has recommended that promotion system of the career development is desired to satisfy and motivate the employee. Moreover, the work appreciation should craft the feeling that they are value for the organization.